Дерматогліфічні маркери карієсу зубів при визначенні рівня інтенсивності процесу у чоловіків із різних регіонів України = Dermatoglyphic markers dental caries when determining the level of intensity of process in men from different regions of Ukraine - M. M. Shinkaruk-Dykovytska (Kazimierz Wielki University, 2015)
Shinkaruk-Dykovytska M. M. дерматогліфічні маркери карієсу зубів при визначенні рівня інтенсивності процесу у чоловіків із різних регіонів України = Dermatoglyphic markers dental caries when determining the level of intensity of process in men from different regions of Ukraine. Journal of Education, Health and Sport. 2015;5(3):79-90. ISSN 2391-8306. DOI: 10.5281/zenodo.16250 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%283%29%3A79-90 https://pbn.nauka.gov.pl/works/547996 http://dx.doi.org/10.5281/zenodo.16250 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 12.03.2015.   УДК 343.982.323:616.314-002   дерматогліфічнІ маркерИ карієсу зубів при визначенні рівня інтенсивності процесу У ЧОЛОВІКІВ ІЗ РІЗНИХ РЕГІОНІВ УКРАЇНИ   DERMATOGLYPHIC MARKERS DENTAL CARIES WHEN DETERMINING THE LEVEL OF INTENSITY OF PROCESS IN MEN FROM DIFFERENT REGIONS OF UKRAINE   М. М. Шінкарук-Диковицька M.M. Shinkaruk-Dykovytska   Вінницький національний медичний університет імені М.І. Пирогова Vinnitsa National Medical University named after Pirogov   Summary. Within each of the 5 studied administrative and territorial regions ofUkraine found dermatoglyphic complexes that enable prediction the development of caries with low or medium levels of intensity of the process. The most capacious by distinguishing ability are dermatoglyphic complexes of southern region, expressed enough - eastern, northern and central regions and less capacious - the western administrative-territorial region ofUkraine. Key words: caries, low and medium intensity lesion, dermatoglyphics, somatically healthy men, administrative and territorial regions of Ukraine.   Резюме. У межах кожного з 5 вивчених адміністративно-територіальних регіонів України виявлені дерматогліфічні комплекси, які дають можливість прогнозу розвитку карієсу з низьким чи середнім рівнями інтенсивності процесу. Найбільш ємкими за розмежовуючою здатністю є дерматогліфічні комплекси південного регіону, достатньо вираженими - східного, північного та центрального регіонів і найменш ємкими - західного адміністративно-територіального регіону України. Ключові слова: карієс, низький і середній рівні інтенсивності ураження, дерматогліфіка, соматично здорові чоловіки, адміністративно-територіальні регіони України.   Резюме. дерматоглИфИчЕСКИЕ маркерЫ карИЕсА зубОв при УСТАНОВЛЕНИИ УрОвня ИнтенсивностИ процесСА У МУЖЧИН ИЗ РАЗНЫХ РЕГИОНОВ УКРАИНЫ. В пределах каждого из 5 изученных административно-территориальных регионов Украины обнаружены дерматоглифические комплексы, которые дают возможность прогноза развития кариеса с низким или средним уровнями интенсивности процесса. Наиболее емкими по раздельной способности являются дерматоглифические комплексы южного региона, достаточно выраженными - восточного, северного и центрального регионов и наименее емкими - западного административно-территориального региона Украины. Ключевые слова: кариес, низкий и средний уровни интенсивности поражения, дерматоглифика, соматически здоровые мужчины, административно-территориальные регионы Украины.